Upwelling intensity and source water properties drive high interannual variability of corrosive events in the California Current - Julia Cheresh; Kristy J. Kroeker; Jerome Fiechter (Scientific Reports, 2023)
Abstract Ocean acidification is progressing rapidly in the California Current System (CCS), a region already susceptible to reduced aragonite saturation state due to seasonal coastal upwelling. Results from a high-resolution (~ 3 km), coupled physical-biogeochemical model highlight that the intensity, duration, and severity of undersaturation events exhibit high interannual variability along the central CCS shelfbreak. Variability in dissolved inorganic carbon (DIC) along the bottom of the 100-m isobath explains 70–90% of event severity variance over the range of latitudes where most severe conditions occur. An empirical orthogonal function (EOF) analysis further reveals that interannual event variability is explained by a combination coastal upwelling intensity and DIC content in upwelled source waters. Simulated regional DIC exhibits low frequency temporal variability resembling that of the Pacific Decadal Oscillation, and is explained by changes to water mass composition in the CCS. While regional DIC concentrations and upwelling intensity individually explain 9 and 43% of year-to-year variability in undersaturation event severity, their combined influence accounts for 66% of the variance. The mechanistic description of exposure to undersaturated conditions presented here provides important context for monitoring the progression of ocean acidification in the CCS and identifies conditions leading to increased vulnerability for ecologically and commercially important species.